2022
DOI: 10.3389/fpls.2022.843911
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association mapping of nutritional traits for designing superior chickpea varieties

Abstract: Micronutrient malnutrition is a serious concern in many parts of the world; therefore, enhancing crop nutrient content is an important challenge. Chickpea (Cicer arietinum L.), a major food legume crop worldwide, is a vital source of protein and minerals in the vegetarian diet. This study evaluated a diverse set of 258 chickpea germplasm accessions for 12 key nutritional traits. A significant variation was observed for several nutritional traits, including crude protein (16.56–24.64/100 g), β-Carotene (0.003–0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 65 publications
0
20
0
Order By: Relevance
“…This process is necessary for the development and expansion of chickpea plants as well as for the production of highquality protein for human consumption. Despite having varied degrees of relatedness, the accessions do not cluster according to their biological components 16 . Hence, we investigated the micronutrients nutritional profiles and their association with EST-SSR markes through modulating the plymorphism analysis, minor allele frequency and heterozygosity level.…”
Section: Resultsmentioning
confidence: 99%
“…This process is necessary for the development and expansion of chickpea plants as well as for the production of highquality protein for human consumption. Despite having varied degrees of relatedness, the accessions do not cluster according to their biological components 16 . Hence, we investigated the micronutrients nutritional profiles and their association with EST-SSR markes through modulating the plymorphism analysis, minor allele frequency and heterozygosity level.…”
Section: Resultsmentioning
confidence: 99%
“…Numerous GWAS have been conducted in chickpea to identify SNPs significantly associated with agronomic traits 48 51 , stress tolerance 52 , 53 , and nutritional traits 20 , 50 , 54 , 55 . However, no GWAS have been reported for fatty acids in chickpea to date.…”
Section: Discussionmentioning
confidence: 99%
“…3 a), which follows previous studies in chickpea 67 . However, some studies reported two or three subpopulations in chickpea 20 , 50 , 54 , 55 . These seven subpopulations represent the diverse ancestral background of chickpea.…”
Section: Discussionmentioning
confidence: 99%
“…Radical developments in genomics techniques have led to the development of various marker systems including mapped microsatellite or simple sequence repeat (SSR) markers, SNPs markers, insertion–deletion (InDel) markers, and more recently haplotype-based SNP markers. Linkage mapping and association mapping are the two most used tools for dissecting the genetics of complex nutritional traits in plants ( Roorkiwal et al., 2022 ). Traditional linkage mapping/QTL mapping explores the recombination events and marker–trait associations (MTAs) in bi-parental segregating populations, such as F 2 , doubled haploid (DH), and recombinant inbred lines (RILs).…”
Section: Breeding Approaches For Enhancing Micronutrient Content In M...mentioning
confidence: 99%
“…This method is very powerful in capturing major genes with larger effects and rare alleles ( Kumar et al., 2016 ). On the other hand, GWAS explores functional variations within genetically diverse panels through linkage disequilibrium (LD) analysis, which is very efficient and effective for identifying new genomic regions ( Yu and Buckler, 2006 ; Roorkiwal et al., 2022 ). Here, we highlight some key genomics efforts undertaken in millets to identify genomic regions associated with grain nutrient content ( Table 2 ).…”
Section: Breeding Approaches For Enhancing Micronutrient Content In M...mentioning
confidence: 99%